A population-based study in resected esophageal or gastroesophageal junction cancer aligned with CheckMate 577. (February 2022) - Pape, Marieke; Vissers, Pauline A.J.; Beerepoot, Laurens V.; van Berge Henegouwen, Mark I.; Lagarde, Sjoerd M.; Mook, Stella; Moehler, Markus; van Laarhoven, Hanneke W.M.; Verhoeven, Rob H.A.
Background: Results of CheckMate 577 show an improved disease-free survival for patients with resected esophageal or gastroesophageal junction cancer treated with adjuvant nivolumab compared with placebo (22.4 versus 11.0 months). Population-based data can provide insights in outcomes from clinical practice. The aim of our study was to investigate disease-free and overall survival in a nationwide population aligned with the inclusion criteria of CheckMate 577. Patients and Methods: Resected patients with stage II/III esophageal or gastroesophageal junction cancer (2015–2016) treated with neoadjuvant chemoradiotherapy were selected from the Netherlands Cancer Registry. Patients with cervical esophageal cancer, irradical resection, or complete pathological response were excluded. Disease-free and overall survival were assessed from 12 weeks after resection using Kaplan-Meier methods. In addition, to adjust for differences in characteristics between CheckMate 577 and our population-based cohort, a matching-adjusted indirect comparison was performed for pathological lymph node status and pathological tumor status. Results: We identified 634 patients. Sixty percent of patients were diagnosed with recurrence or were deceased at the end of follow-up. Median disease-free survival was 19.7 months and median overall survival was 32.2 months. After the matching procedure, the median disease-free survival was 17.2 months and median overall survival was 28.2 months. Conclusions: Disease-free survival in our population-based study was considerably longer than the placebo population of CheckMate-577 (19.7 versus 11.0 months). Possible explanations are differences in characteristics, quality of esophageal cancer care, or differential strategies for evaluation of recurrence. In the Netherlands postoperative imaging is not part of the standard follow-up as opposed to the standard postoperative imaging in the CheckMate 577 trial. The difference in postoperative imaging could partially explain the longer disease-free survival observed in our study. Quality and optimization of current treatment modalities remain important aspects of esophageal cancer care.